PENGARUH PENGHINDARAN PAJAK DAN BIAYA AGENSI TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdapat di Bursa Efek Indonesia tahun 2017-2020) - Frista Veronica; Anik Malikah; Afifudin Afifudin (Universitas Islam Malang, 2022)
This research aims to determine whether tax avoidance and agency cost have a significant effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange. The sample used in this research to 20 manufacturing companies listed on the Indonesia Stock Exchange that provide complete financial reports and earn profits after 2017-2020. The sampling technique in this research used purposive sampling in accordance with the criteria used in the research. This research uses a quantitative approach that aims to explain the effect of the independent variables, namely tax avoidance and agency cost. The data analysis method used in this research is multiple linear regression. The results of this research indicate that (1) tax avoidance has so no significant effect on firm value.(2) agency cost have a significant effect on firm value. Keywords : tax avoidance and agency cos have a significant effect on firm value